One loop conformal invariance of the superstring in an AdS(5) x S-5 background - Vallilo, B. C. (Int School Advanced Studies, 2002)
It is proven that the pure spinor superstring in an AdS(5) x S-5 background remains conformally invariant at one loop level in the sigma model perturbation theory.
Keywords: superstrings and heterotic strings; conformal field models in string theory